Filariasis Control in Coastal Nigeria: Predictive Significance of Baseline Entomological Indices of Anopheles gambiae s.l. (Diptera: Culicidae). (10th January 2013) - Uttah, Emmanuel C.; Ibe, Dominic; Wokem, Gloria N.
Abstract : This work aimed at collecting filariasis transmission data of Anopheles gambiae to be used in predicting future trends in filariasis transmission and control programme outcomes. Collection of the mosquitoes was made by human landing catch and light trap methods. In all, 5, 813 females were caught from September 2005 to August 2006. Mosquito population started to expand at the onset of the rains. The highest density was found after peak temperature. The A. gambiae s.l. biting peaked around midnight; 39.7% were parous and 0.3% were infective. The highest percentage of parous females caught was near midnight, ranging between 42.0% and 47.5% from 22.00 to 03.00 hours. Biting rate in the rainy season was 2.6 times higher than it in the dry season. Transmission potential was 3.6 times higher during the rains than during the dry season. The percentage infectivity was relatively high (13.2%) in June, corresponding to 8.8 infective bites per person per month. All infective A. gambiae, were caught between 22.00 and 03.00 hours. The average load of L3 larvae per infective A. gambiae was 1.4 L3/mosquito. The monthly transmission potential calculated for each month indicated that transmission was ongoing for most of the months of the year, especially in the rainy season.